Re-imagining freedom as elderly female porters: A study of buruh gendong at Beringharjo traditional market of Yogyakarta - Gilang Mahadika; Setiadi Setiadi (Universitas Trunojoyo Madura, 2021)
This paper expects to reveal the struggle of elderly female porters or buruh gendong who mostly had a historical background of working in industrial production (factory) but ended up being self-employed at Beringharjo traditional market of Yogyakarta. They used to work as factory workers. However, most factories collapsed in the aftermath of the 1997 economic crisis, especially in Southeast Asia. These older people from peri-urban (and rural) areas with lower-class status ended up in urban areas to be self-employed and became precarious workers. Therefore, the research questions are how they cope with the income uncertainties only to meet their daily needs and still desire their children to have a better living condition. Observations and interviews were done with 25 elderly female traditional porters as the research methods from 2020. They are primarily in the age range of late 50-80 years old. The results show that income uncertainties and social insecurity bring about precariousness. Buruh gendong have to work every day only to make ends meet. However, these conditions could also open up alternative perspectives that they often found themselves liberated from the control of industrial production. They do not work for capital owners or bosses; they work for themselves (self-employed). They are free or more flexible on working hours, but, at the same time, they have to accept their insecure employment. Buruh gendong also have desires for their children to be able to achieve a higher education level. Eventually, the desires are mostly unfulfilled; their children get unfortunate work and still live barely.